Children with trisomy 21 are a group at risk for severe COVID-19: Case reports from a COVID-19 treatment unit in Addis Ababa, Ethiopia - Alemayehu, Tinsae; Buonsenso, Danilo (Frontiers in Pediatrics, 2022)
Trisomy 21 (Down syndrome) is a chromosomal disorder associated with humoral and cellular immunologic impairments among other systemic manifestations. It occurs at a frequency of 1 in 750 live births. There are increasing reports of children with Down syndrome presenting signs of severe COVID-19. The literature from Africa on pediatric COVID-19 and risk stratification for severe disease is scant. A summary of the clinical features, complications and treatment outcomes of three Ethiopian children with Trisomy 21 and severe COVID along with a discussion of the correlation of Trisomy 21 immunology and severe SARS CoV-2 infection is presented